Radio programming : tactics and strategy - Norberg, Eric G. (Broadcasting & cable series., 2016)
A practical handbook for programming directors, this guide focuses on achieving specific objectives in today's modern, competitive environment. Radio Programming is designed to convey underlying principles and to assist the programmer in accomplishing specific objectives, without mandating exact implementation methods. Instead, it empowers station management and the PD to implement strategies that will work for the particular format and market niche. Radio Programming will be helpful for neophytes in programming, experienced programmers seeking further growth, air talent seeking to develop skills, and general managers trying to understand programming and effectively manage program directors without stifling creativity. It will also help general managers hire effective programmers. Eric Norberg is the editor and publisher of the Adult Contemporary Music Research Letter and a radio consultant. He has worked as a program director at several radio stations, as on-air talent and general manager, and has also operated a radio production company. For fourteen years he has written a weekly column on radio programming for The Gavin Report, a radio trade publication.